2023
DOI: 10.17129/botsci.3242
|View full text |Cite
|
Sign up to set email alerts
|

Una nueva especie de Chthamalia (Apocynaceae; Asclepiadoideae; Gonolobeae; Gonolobinae), endémica a Puebla, México

Abstract: Antecedentes: Chthamalia es un género de Gonolobinae distintivo por su hábito trepador o rastrero, sus flores de hasta dos centímetros de diámetro y su corona ginostegial ciatiforme con apéndices generalmente lineares. Ocho especies han sido reportadas en México, pero ninguna de ellas corresponde al taxón estudiado. Pregunta y/o Hipótesis: ¿Cuáles son las características que diferencian a los individuos del presente taxón con respecto a otras especies de Chthamalia? ¿Cuál es su distribución y estado de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…(Morillo, 2023b), and Trichosacme Zucc. (Alvarado-Cárdenas and Cortez, 2022), or established new genera (Morillo, 2012(Morillo, , 2013(Morillo, , 2015(Morillo, , 2016(Morillo, , 2023aMorillo et al, 2013Mangelsdorff et al, 2016;Keller and Liede-Schumann, 2020;Alvarado-Cárdenas, 2021). It has been suggested that Matelea s.s. (sensu Krings and Morillo, 2015;Morillo, 2015;Morillo et al, 2017Morillo et al, , 2023 only contains around 20 species, morphologically consistent with the type species M. palustris Aubl.…”
Section: Introductionmentioning
confidence: 99%
“…(Morillo, 2023b), and Trichosacme Zucc. (Alvarado-Cárdenas and Cortez, 2022), or established new genera (Morillo, 2012(Morillo, , 2013(Morillo, , 2015(Morillo, , 2016(Morillo, , 2023aMorillo et al, 2013Mangelsdorff et al, 2016;Keller and Liede-Schumann, 2020;Alvarado-Cárdenas, 2021). It has been suggested that Matelea s.s. (sensu Krings and Morillo, 2015;Morillo, 2015;Morillo et al, 2017Morillo et al, , 2023 only contains around 20 species, morphologically consistent with the type species M. palustris Aubl.…”
Section: Introductionmentioning
confidence: 99%
“…Citizen science platforms have been demonstrated to play a very important role in terms of biodiversity documentation (Spear et al, 2017;Soteropoulos et al, 2021;Alvarado-Cárdenas et al, 2023), and the case of S. papyracanthus is not an exception. In 2020, the first record of a putative individual of the species was uploaded to the Naturalista 1 Universidad de Guadalajara, Centro Universitario de Ciencias Biológicas y Agropecuarias, Departamento de Botánica y Zoología, 45200 Zapopan, Jalisco, Mexico.…”
Section: Introductionmentioning
confidence: 99%